Optimization of Distribution Cost (a Case study in PT. Zamrud Bumi Indonesia) - Shilvaisnaeni Regia; Robi Awaluddin; Ayus Ahmad Yusuf (Journal of Agri Socio Economics and Business, 2021)
PT. Zamrud Bumi Indonesia is a manufacturing company engaged in the processing of multipurpose liquid organic agricultural fertilizer branded Power Bumi. Distribution from warehouses to destinations that vary in distance resulted in different distribution cost budgets. Transportation models can help solve the problem of distributing products from multiple warehouses to multiple destination cities and reduce total distribution costs. This study aims to find out the total minimum cost of distribution by using the Least Cost method as the initial solution and knowing the test results of MODI method as the optimum solution at PT. Zamrud Bumi Indonesia. The results of this study showed that before using the Transportation Method, the company incurred a distribution fee of Rp. 11.600.000,- in December 2020, after using the Least Cost transportation method as the initial solution of distribution costs incurred in the amount of Rp. 9.981.250,- and modi transportation method as the optimum test resulted in the same value of Rp. 9,981,250. So the company saves distribution costs of Rp. 1.618.750,- every month